Development of Smartphone-Based Digital Image Colorimetry Assay for the Simple and Efficient Determination of Total Acid Content in Apple Vinegar Samples - Kustanto, Tulay Borahan; Bakirdere, Sezgin (WILEY-V C H VERLAG GMBH, 2025)
A simple, fast, and environmentally friendly colorimetric assay utilizing a natural indicator was developed for determination of total acid content in apple vinegar samples. A smartphone was implemented with a digital image colorimetric system as the detector. Hibiscus extract was used as a natural indicator. Influential parameters, including the volumes of hibiscus extract, ammonium acetate, and deionized water, were investigated and optimized. The colorimetric response demonstrated a linear correlation with increasing acetic acid concentration. RGB (red, green, and blue) color values were extracted from the captured digital images using the Color Detector application and used as the analytical data. The linear range of the developed method was found to be 0.020-0.20 M. The accuracy of the developed method was evaluated against a standard titration method. The developed method exhibits good linearity (R-2 = 0.9980), precision (%RSD < 10), and superior advantages in speed and accessibility. The consistent relationship between the developed method's colorimetric results and standard titration values demonstrates the reliability of this approach as an effective screening tool for quality control, especially in resource-limited settings where conventional equipment is unavailable.
Keywords: Colorimetry; Digital image; Smartphone; Total acid content; Vinegar; BACTERIA; Chemistry